Primary Language Teacher Education in Italy: Refining Syllabus Design by Listening to Learners’ Voices - Poppi, Franca; Bondi, Marina (Íkala, Revista de Lenguaje y Cultura, 2009)
Decisions concerning syllabus design are generally based on considerations linked to the level of competence to be attained by the end of the course. The Common European Framework of Reference is one of the many yardsticks against which language competence can be measured. However, the guidelines it provides may need further qualifications, especially when dealing with foreign-language primary school teaching. This paper sets out to examine how the opinions of a group of primary school teachers who have been trained to become English teachers can be exploited for the purpose of refining syllabus design for further training courses. Received: 18-11-07/ Accepted: 14-01-09 How to reference this article: Poppi, F. & Bondi, M. (2009). Primary Language Teacher Education in Italy: Refining Syllabus Design by Listening to Learners’ Voices. Íkala. 14(1), pp.161-194.